Designing a Digital Technology-Based Interactive Museum Prototype as an Effort to Enhance Education and Cultural Preservation in Indonesia - Chairul Rizal; Erni Marlina Saari (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
Museums play an important role in the preservation of cultural heritage and public education. However, the changing behavior of the younger generation, who are more interested in digital media, is leading to a further decline in visits to conventional museums. This research aims to design a digital technology-based interactive museum prototype as an effort to enhance education and cultural preservation in Indonesia. The research method uses a Research and Development (R&D) approach with the stages of needs analysis, system design, prototype development, and user testing. The research instruments include the System Usability Scale (SUS) and semi-structured interviews with 30 respondents. The research results show that the interactive museum prototype has an average SUS score of 75.6, which falls into the very good category, and received positive feedback regarding increased visitor engagement in understanding cultural collections. This research contributes to the development of a digital museum model that meets the needs of Indonesian society.